2009
DOI: 10.1007/s00221-009-2019-7
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements affirm: automatic overt gaze and arrow cueing for typical adults and adults with autism spectrum disorder

Abstract: People with autism spectrum disorder (ASD) show reduced interest towards social aspects of the environment and a lesser tendency to follow other people's gaze in the real world. However, most studies have shown that people with ASD do respond to eye-gaze cues in experimental paradigms, though it is possible that this behaviour is based on an atypical strategy. We tested this possibility in adults with ASD using a cueing task combined with eye-movement recording. Both eye gaze and arrow pointing distractors res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 65 publications
9
72
7
Order By: Relevance
“…The findings extend previous research by comparing the effect of biological (eye gaze and finger pointing) and non-biological (arrows and words) cues on anti-saccade task performance. Although previous studies using simple saccadic tasks found that both gaze and arrow cues facilitate saccadic orienting (Kuhn and Benson 2007;Kuhn and Kingstone 2009;Kuhn et al 2010), the present findings, using a more complex task, suggest that socially relevant biological cues have privileged access to the oculomotor system. In experiment 1, eye gaze but not arrow cues caused participants to make faster anti-saccades in the opposite direction to the cues.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The findings extend previous research by comparing the effect of biological (eye gaze and finger pointing) and non-biological (arrows and words) cues on anti-saccade task performance. Although previous studies using simple saccadic tasks found that both gaze and arrow cues facilitate saccadic orienting (Kuhn and Benson 2007;Kuhn and Kingstone 2009;Kuhn et al 2010), the present findings, using a more complex task, suggest that socially relevant biological cues have privileged access to the oculomotor system. In experiment 1, eye gaze but not arrow cues caused participants to make faster anti-saccades in the opposite direction to the cues.…”
Section: Discussioncontrasting
confidence: 87%
“…The results of Kuhn and colleagues (Kuhn and Benson 2007;Kuhn and Kingstone 2009;Kuhn et al 2010) and those of the multitude of studies which have found no differences between the effects of biological and non-biological cues on covert attention, are somewhat counterintuitive. Eye gaze is clearly an important aid in social interaction which is processed and interpreted without effort in everyday life, with some evidence suggesting that gaze following may even be present from birth (Farroni et al 2002(Farroni et al , 2004.…”
Section: Introductionmentioning
confidence: 94%
“…For example, there are more similarities than differences in eye movements between TD and ASD groups for simple rule based tasks in the attentional (Kuhn et al, 2010) and the social domains (Benson & Fletcher-Watson, 2011). Whereas for more complex abstract reasoning tasks where there is ambiguity with relation to target items , or where value judgements rely on top down knowledge , there are early processing differences indicating that initial orienting to, and immediate detection of weird target items in scenes is absent in ASD.…”
Section: Looking Seeing and Believing In Autism 2 Lay Abstractmentioning
confidence: 99%
“…Alternatively, the Complex Information Processing theory (Minshew & Goldstein, 1998) for a range of tasks that are more in line with Minshew and Goldstein's (1998) theory, than with any other. For example, there are more similarities than differences in eye movements between TD and ASD groups for simple rule based tasks in the attentional (Kuhn et al, 2010) and the social domains (Benson & Fletcher-Watson, 2011 where value judgements rely on top down knowledge , there are early processing differences indicating that initial orienting to, and immediate detection of weird target items in scenes is absent in ASD. Moreover, the time to respond and to locate the weird target items was modulated by whether or not the pictures had people in them ).…”
Section: Haim Et Al 2006)mentioning
confidence: 99%
“…The evaluation of the eye gaze response of autistic children to arrow cues showed that the arrow image is accepted as a prompt for orienting or attention. It has also been addressed that the response to arrow cues is an automatic phenomenon [22][23][24].…”
Section: Introductionmentioning
confidence: 99%